Regional Features of Small and Medium Business Development in Ukraine (Ivano-Frankivsk City Example) - Yurii DRUK; Nataliya MARCHUK; Vasyl MARCHUK (Communications of International Proceedings, 2020)
The effective functioning of small and medium enterprises in Ukraine is due to multifactorial impact formation of a competitive environment according to the deepening market relations. The approval of positive trends and the implementation of measures to improve business in the regions are directly dependent on the formation of purposeful, consistent and predictable state regulatory policy and actions of government and administrative bodies in the field of economic activity. At the same time, there are also ways to create a unique business environment and promote entrepreneurship at the local level. The experience of Ivano-Frankivsk city has shown high efficiency in the involvement of favorable geographical location, government interest and willingness to promote business development.
Keywords: Small and Medium Enterprises; Business Environment; Economic Development; Investment.